THERMODYNAMICS ANALYSIS TO EVALUATE THE COMBUSTION PROCESS OF E50 FUEL WITH INJECTION VOLUME VARIATION - Paloboran, Marthen; Darmawang; Pagasis, Thomas; Atarezcha Pangruruk, Thesya (Journal of Applied Engineering Science, 2026)
The study is based on the first and second laws of thermodynamics to investigate and analyze the performance of spark ignition engines with varying injection durations of the gasoline and bioethanol fuel blend (E50). Experiments were conducted using standard parameters of engines, including an 11:1 compression ratio and 12 bTDC of ignition timing. The injection volume of the fuel blend was set at 100% to 200% (increment of 25%) of the injection volume of gasoline. The effect of the injection volume of E50 is evident in various performance indicators, including brake-specific fuel consumption (BSFC), thermal efficiency, and brake power, as observed in both energy and exergy analyses. The most important conclusion of this study is that the performance of the engine using E50 would be similar to gasoline (E0), both in energy and exergy analyses, when the injection volume of E50 increased by 25% compared to gasoline.
Keywords: energy and exergy, mass flow rate, gasoline, bioethanol, thermodynamic law